Financial Statement Analysis in Measuring Financial Performance in PT. Ace Hardware Tbk - Afif, Muhammad Naufal; Rofi’ah, Dewi; Najib, Thoha Ainum (Jurnal Akuntansi Bisnis dan Ekonomi, 2024)
This research aims to determine the financial performance of PT. Ace Hardware Indonesia Tbk from ratio calculations. This research uses qualitative methods and the focus of this research is on the annual financial reports of PT. Ace Hardware Indonesia Tbk 2022-2023 has been published on www.idx.co.id. The data source used in this research is secondary data, namely data from financial reports that have been audited and are available to the necessary parties. The data collection method used is the documentation method. This includes the process of observing, recording, grouping, and using secondary data from documents obtained from the website www.idx.co.id, such as PT financial reports. Ace Hardware Indonesia Tbk for the 2019-2023 period. The analysis used in the research is financial report analysis which is used to analyze how the financial reports of PT. Ace Hardware Indonesia Tbk. 2019-2023 using profitability, liquidity, solvency and activity ratios. The results of the financial report analysis consist of Liquidity Ratios, Solvency Ratios, Activity Ratios and Profitability Ratios, so that companies have the ability to determine and make management decisions related to company performance.